2015
DOI: 10.1093/annonc/mdv317
|View full text |Cite
|
Sign up to set email alerts
|

FLORENCE: a randomized, double-blind, phase III pivotal study of febuxostat versus allopurinol for the prevention of tumor lysis syndrome (TLS) in patients with hematologic malignancies at intermediate to high TLS risk

Abstract: NCT01724528.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 18 publications
0
48
0
3
Order By: Relevance
“…Serum uric acid levels at days 2 and 7 were found to be significantly lower than the baseline values in patients treated with febuxostat. Compared to allopurinol, febuxostat achieved similar serum uric acid levels at day 2 in 2 studies, while significantly lower values were reported in largest RCT . Correspondingly, day 7 serum uric acid did not differ between the 2 groups in 2 studies, while another 2 observed that febuxostat leads to significantly lower values.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Serum uric acid levels at days 2 and 7 were found to be significantly lower than the baseline values in patients treated with febuxostat. Compared to allopurinol, febuxostat achieved similar serum uric acid levels at day 2 in 2 studies, while significantly lower values were reported in largest RCT . Correspondingly, day 7 serum uric acid did not differ between the 2 groups in 2 studies, while another 2 observed that febuxostat leads to significantly lower values.…”
Section: Resultsmentioning
confidence: 81%
“…The most important methodological characteristics (study design, exclusion criteria, population and disease type, criteria for TLS diagnosis and response definition, timing and dosage of febuxostat and allopurinol) of the included studies are described in Table . Three studies were RCTs, while the rest 3 were observational with a cohort design . Patients with severe kidney impairment were excluded from the majority of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bei wiederholten Cisplatindosen von >100 mg/m 2 ist die Gabe von Mannitol mit einem verminderten Auftreten von AKI assoziiert [55]. Eine Präventionsmaßnahme für Patienten mit einem hohen Risiko für ein Tumorlysesyndrom ist die Gabe von Xanthinoxidaseinhibitoren [74]. Die im deutschsprachigen Raum tätige iCHOPGruppe ("intensive care in hematologic-oncologic patients") stellt auch das Thema AKI in das Zentrum ihrer fortlaufenden Analysen [70].…”
Section: Patienten Mit Hämato-onkologischen Erkrankungenunclassified